Airborne microbial counts in the oral medicine section, University of the Philippines College of Dentistry - Manansala, Katrina M.; Puzon, Mical Ellaine (Department of Community Dentistry, University of the Philippines Manila, 2015)
Methods: This study has a comparative and cross-sectional design. Passive sampling was done using 10 settle plates randomly distributed around the Oral Medicine Section for 3 rounds, 7 o'clock (at rest), 12 o'clock, and 4 o'clock (in operational). The collection was done following Fisher's schedule of 1/1/1, wherein the plates were placed 1 meter from the floor, 1 meter from the wall, and opened for 1 hour. The procedures done in the morning and afternoon on each dental unit were noted. After collection, the plates were incubated at 37°C for 48 hours. Non-parametric, Kruskal-Wallis test was used to determine the level of significance in the mean values of CFU counts among the three rounds. Pearson correlation test was used to evaluate the association between the CFU counts with the number of people, as well as the relationship of CFU counts with the procedures performed.